2019
DOI: 10.31557/apjcp.2019.20.5.1587
|View full text |Cite
|
Sign up to set email alerts
|

Ionizing Radiation-inducible microRNA-21 Induces Angiogenesis by Directly Targeting PTEN

Abstract: Background:Previous experimental studies have established that MicroRNAs (miRNAs) can function as oncogenes or tumor suppressors in the regulation of tumor biology or pathology. However, the effects of ionizing radiation (IR) on the expression levels of cellular miRNAs and their further effects on the biological behavior of tumor cells require further investigation.Methods:We determined the proliferation, migration and tube formation of HUVEC cells after ionizing radiation (control, 0h and 24h), and the change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…MiR-221-5p inhibition restored the expression of EPAS1 but not EFNB2, and miR-21a-3p inhibition restored the expression of E2F8 but not EPAS1. MiR-21 had been reported to increase proliferation, migration and tube formation of Human Umbilical Vein Endothelial Cells (HUVECs) and induce angiogenesis by directly targeting PTEN [30, 31]. Moreover, miR-21a-3p and its downstream target E2F8 were further studied.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-221-5p inhibition restored the expression of EPAS1 but not EFNB2, and miR-21a-3p inhibition restored the expression of E2F8 but not EPAS1. MiR-21 had been reported to increase proliferation, migration and tube formation of Human Umbilical Vein Endothelial Cells (HUVECs) and induce angiogenesis by directly targeting PTEN [30, 31]. Moreover, miR-21a-3p and its downstream target E2F8 were further studied.…”
Section: Resultsmentioning
confidence: 99%
“…MiR-21 promotes tumorigenesis in MM, glioblastoma and prostate cancer via inhibition of pivotal tumor suppressors ( Figure 3 ) [ 33 , 40 , 49 , 50 , 72 , 114 , 115 ]. MiR-21 modifies the extracellular matrix by suppressing critical inhibitors of matrix metalloproteinases including TIMP3 and RECK [ 55 , 56 , 116 ].…”
Section: Exosome-mediated Mir-21 Transportmentioning
confidence: 99%
“…In fact, increased expression of miR-21 enhances the invasive potential of MM cells through TIMP3 inhibition [ 56 ]. Furthermore, miR-21 induces tumor angiogenesis through targeting PTEN, activating AKT and ERK1/2 signaling, thereby enhancing HIF-1α and VEGF expression as well as by targeting FASLG and angiotensin II [ 115 , 117 , 118 , 119 , 120 ].…”
Section: Exosome-mediated Mir-21 Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, miR-21, the star oncomiRNA, has been reported to perform its pro-tumor function in conjunction with radiation (Liu et al 2011 ). Zhang et al ( 2019 ) had identified a functional link between IR-inducible miR-21 and angiogenesis that promotes metastasis, invasion and growth of tumors. Ionizing radiation induced miR-21 overexpression, which in turn downregulated expression of PTEN and finally induced angiogenesis via increased vascular endothelial growth factor A (VEGF) and HIF-1α expression through the PI3K/AKT pathway.…”
Section: Introductionmentioning
confidence: 99%